KINEMATICS OF THE EAST AFRICAN RIFT FROM GPS AND EARTHQUAKE SLIP VECTOR DATA - Calais E.; Ebinger C.J.; Hartnady C.; Nocquet J.M. (My University, 2006)
Although the East African Rift (EAR) System is often cited as the archetype for models of continental rifting and break-up, its present-day kinematics remains poorly constrained. We show that the currently available GPS and earthquake slip vector data are consistent with (1) a present-day Nubia-Somalia Euler pole located between the southern tip of Africa and the Southwest Indian ridge and (2) the existence of a distinct microplate (Victoria) between the Eastern and Western rifts, rotating counter-clockwise with respect to Nubia. Geodetic and geological data also suggest the existence of a (Rovuma) microplate between the Malawi rift and the Davie ridge, possibly rotating clockwise with respect to Nubia. The data indicate that the EAR comprises at least two rigid lithospheric blocks bounded by narrow belts of seismicity (<50 km wide) marking localized deformation rather than a wide zone of quasi-continuous, pervasive deformation. On the basis of this new kinematic model and mantle flow directions interpreted from seismic anisotropy measurements, we propose that regional asthenospheric upwelling and locally focused mantle flow may influence continental deformation in East Africa. © The Geological Society of London 2006.